2008
DOI: 10.2535/ofaj.85.43
|View full text |Cite
|
Sign up to set email alerts
|

The bite-raised condition enhances the aging process in the dorsal and ventral hippocampus

Abstract: Summary:The bite raised condition decreases the number of neurons and increases the amount of glial fibrillary acidic protein in the hippocampus of aged SAMP8 mice. In the present study, we examined whether these effects differ between the dorsal and ventral hippocampus. In bite-raised SAMP8 mice, the number of neurons was significantly lower in the hippocampal CA1 and dentate gyrus (DG) subfields compared to control mice. In the bite raised condition, the number of neurons was significantly lower in both the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The systemic effects of long-term masticatory imbalances are associated with neurodegeneration and are a risk factor for senile dementia in humans [4] and memory deficits in experimental animals [5]. To investigate the impact of masticatory imbalances on various activities and physiological factors, experimental masticatory deprivation has been modelled experimentally in animals using a modified diet [6], molar removal [7,8], or occlusion disharmony modelled by "bite-raised" condition [9,10]. These approaches revealed that masticatory dysfunction reduces spatial learning and memory in water maze tests in rats [8,11] and mice [11-13], and that these deficits seem to increase with aging and time after tooth loss [8].…”
Section: Introductionmentioning
confidence: 99%
“…The systemic effects of long-term masticatory imbalances are associated with neurodegeneration and are a risk factor for senile dementia in humans [4] and memory deficits in experimental animals [5]. To investigate the impact of masticatory imbalances on various activities and physiological factors, experimental masticatory deprivation has been modelled experimentally in animals using a modified diet [6], molar removal [7,8], or occlusion disharmony modelled by "bite-raised" condition [9,10]. These approaches revealed that masticatory dysfunction reduces spatial learning and memory in water maze tests in rats [8,11] and mice [11-13], and that these deficits seem to increase with aging and time after tooth loss [8].…”
Section: Introductionmentioning
confidence: 99%
“…SAMP8 mice reach adult maturity at 6 months of age when learning and memory deficits become apparent in a variety of behavioural tests [42-45] and when reduced masticatory activity accelerates age-related learning and memory decline [40]. Occlusal disharmony also aggravates age-dependent deficits in spatial learning in the Morris water maze [17,46-49]; see [13,40] for recent reviews. Moreover, monkey studies demonstrate that when occlusal disharmony is removed, the associated stressful response disappears [50].…”
Section: Discussionmentioning
confidence: 99%